Identity, Self-Awareness, and Self-Deception: Ethical Implications for Leaders and Organizations - Caldwell, Cam (Journal of business ethics, 2009)
The ability of leaders to be perceived as trustworthy and to develop authentic and effective relationships is largely a function of their personal identities and their self-awareness in understanding and making accommodations for their weaknesses. The research about self-deception confirms that we often practice denial regarding our identities without being fully aware of the ethical duties that we owe to ourselves and to others. This article offers insights about the nature of identity and self-awareness, specifically examining how self-deception can create barriers to self-awareness within both a personal and a business context.